The Effects of Fiscal Policy on Households during the COVID-19 Pandemic - Dzung Bui; Lena Dräger; Bernd Hayo; Giang Nghiem (ZBW - Leibniz Information Centre for Economics, 2021)
In response to the spillovers of the COVID-19 pandemic on the economy, many governments paid cash transfers to households. We examine the effect of this fiscal policy instrument on households in two emerging economies, Vietnam and Thailand. Our analysis is based representative population surveys conducted in these countries during the pandemic in 2020. We find that government financial support improves consumer sentiment and increases the likelihood of durable spending. Possibly channels through which financial support affects consumer sentiment are creating more optimism about macroeconomic expectations, raising trust in the government's ability to deal with the pandemic's effect on the economy, lowering general concerns about the impacts of the crisis. We also find that the financial support improves individuals' mental health and life satisfaction. Our results suggest that financial support not only helps stimulate the economy but also enhances people's well-being more generally.
Keywords: E21; E62; 330; Fiscal policy; Cash transfer; Consumer sentiment; Expectations; Government Trust; COVID-19; Thailand; Vietnam